From Migration to Memory: The Preservation of the Lithuanian Diaspora Heritage in Argentina, Brazil, and Uruguay (Relevant Tomorrow / Aktualu rytoj, 2025)
The article discusses the preservation of the Lithuanian diaspora heritage in Argentina, Brazil, and Uruguay, focusing on the role of migration museums, archives, cultural institutions, and community initiatives. Despite the large Lithuanian diaspora in South America, the mechanisms for preserving its heritage have been little researched. The article aims to assess the role of memory institutions and local communities in documenting and preserving Lithuanian identity, and to identify the main challenges of this process in Argentina, Brazil, and Uruguay. It has been found that the migration museums in São Paulo, Buenos Aires, and Montevideo, as well as the Centre for Latin American Migration Studies in Argentina, contribute significantly to the documentation and digitisation of migration heritage; however, the efforts remain fragmented. A case study of Lituanika neighbourhood in São Paulo, Brazil, shows that although local community initiatives can serve as an alternative form of heritage preservation, the sustainability of such activities has been limited by material and institutional factors. The preservation of diaspora heritage depends on institutional resources and (deeper) community involvement; therefore, by adopting a forward-looking approach and continuously investing in human (especially community) and technological (primarily digitisation) resources, the cultural heritage of Lithuanian migrants in South America can be preserved in a more sustainable way for future generations.
Keywords: Lithuanian diaspora; migration archives; diaspora heritage; Lituanika; Centre for Latin American Migration Studies; Argentina; Brazil; Uruguay